Antifungal, anti-biofilm, and anti-hyphal properties of N-substituted phthalimide derivatives against Candida species - Shaik, Shamshe; Lee, Jin-Hyung; Kim, Yong-Guy; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2024)
Candida species are a ubiquitous pathogenic fungal genus responsible for causing candidiasis.They are one of the primary causatives of several mucosal and systemic infections in humans and are adept at survival in various environments. We investigated the antifungal, antibiofilm, and antihyphal effects of six N-substituted phthalimides against three Candida species. Of the derivatives, N-butyl phthalimide (NBP) was the most potent with MIC of 100 µg/ml and dosedependently inhibited biofilm at sub-inhibitory concentrations (10-50 µg/ml) in both fluconazoleresistant and -sensitive C. albicans as well as C. parapsilosis. NBP also effectively inhibited biofilm formation in other pathogens like uropathogenic Escherichia coli, S. epidermidis, S. aureus, and V. parahaemolyticus along with polymicrobial biofilm of S. epidermidis and C. albicans. NBP markedly inhibited C. albicans hyphal formation, and cell aggregation and altered the colony morphology in a dose-dependent manner. Gene expression analysis shows that NBP significantly downregulated the expression of important hyphae and biofilm-associated genes ECE1, HWP1 and UME6 on NBP treatment. NBP exhibited mild toxicity at concentrations ranging from 2-20 µg/ml in a nematode model. Therefore, this study suggests that NBP has antibiofilm and antifungal potential against various Candida strains.